80‐1: Invited Paper: Developing AMQLED Technology for Display Applications. Issue 1 (30th May 2018) - Li, Yanzhao; Chen, Zhuo; Kristal, Boris; Zhang, Yuanming; Li, Dong; Yu, Gang; Wang, Xiyuan; Wang, Long; Shi, Yongming; Wang, Zhiliang; Chen, Youru; Yu, Jing; et al.
Abstract : In this paper we describe current state of the active matrix quantum dot light emitting diode (AMQLED) display technology and analyze the ways this technology can be developed for mass‐production. We discuss material requirements, device structures, electrical and optical properties of quantum dot light emitting diodes (QLED). We also show how active matrix displays based on quantum dot light emitting diodes (QLED) in a near future can provide a compelling alternative to the OLED and LCD based displays.